Slowly Adapting Sensory Units Have More Receptors in Large Airways than in Small Airways in Rabbits - Liu, Jun; Song, Nana; Guardiola, Juan; Roman, Jesse; Yu, Jerry (Frontiers in Physiology, 2016)
Sensory units of pulmonary slowly adapting receptors (SARs) are more active in large airways than in small airways. However, there is no explanation for this phenomenon. Although sensory structures in large airways resemble those in small airways, they are bigger and more complex. Possibly, a larger receptor provides greater surface area for depolarization, and thus has a lower activating threshold and/or a higher sensitivity to stretch, leading to more nerve electrical activities. Recently, a single sensory unit has been reported to contain multiple receptors. Therefore, sensory units in large airways may contain more SARs, which may contribute to high activities. To test this hypothesis, we used a double staining technique to identify sensory receptor sizes. We labeled the sensory structure with Na+/K+-ATPase antibodies and the myelin sheath with myelin basic protein (MBP) antibodies. A SAR can be defined as the end formation beyond MBP labeling. Thus, we are able to compare sizes of sensory structures and SARs in large (trachea and bronchi) vs small (bronchioles <500um in diameter) airways in the rabbit. We found that even though the sensory structure was bigger in large airways than in small airways (3,340±223 vs 1,168±103 um2; P<0.0001), there was no difference in receptor sizes (349±14 vs 326±16 um2; P>0.05). However, the sensory structure contains more SARs in large airways than in small airways (9.6±0.6 vs 3.6±0.3; P<0.0001). Thus, our data support the hypothesis that greater numbers of SARs in sensory units of large airways may contribute to higher activities.